Experimental Investigation and CFD Modeling of Supercritical Adsorption Process - Lebedev, Artem (Polymers (Basel), 2020)
The kinetics of the supercritical adsorption process was experimentally studied by the example of ”ibuprofen-silica aerogel” composition obtainment at various parameters: Pressure 120–200 bar and temperature 40–60 °C. Computational Fluid Dynamics (CFD) model of the supercritical adsorption process in a high-pressure apparatus based on the provisions of continuum mechanics is proposed. Using supercritical adsorption process kinetics experimental data, the dependences of the effective diffusion coefficient of active substance in the aerogel, and the maximum amount of the adsorbed active substance into the aerogel on temperature and pressure are revealed. Adequacy of the proposed model is confirmed. The proposed mathematical model allows predicting the behavior of system (fields of velocity, temperature, pressure, composition, density, etc.) at each point of the studied medium. It makes possible to predict mass transport rate of the active substance inside the porous body depending on the geometry of the apparatus, structure of flow, temperature, and pressure.